Family upheaval : generation, mobility and relatedness among Pakistani migrants in Denmark - Rytter, Mikkel (EASA series, 2013)
Pakistani migrant families in Denmark find themselves in a specific ethno-national, post-9/11 environment where Muslim immigrants are subjected to processes of non-recognition, exclusion and securitization. This ethnographic study explores how, why, and at what costs notions of relatedness, identity, and belonging are being renegotiated within local families and transnational kinship networks. Each entry point concerns the destructive-productive constitution of family life, where neglected responsibilities, obligations, and trust lead not only to broken relationships, but also, and inevitab.